Factores de Riesgo de Complicaciones Hemodinámicas tras Exposición a Anestesia Raquídea en Gestantes Cesareadas del Hospital Regional Docente de Trujillo de Enero del 2017-Enero del 2018 - Rengifo Pinedo, Katty Lorena (2019)
Regional anesthesia techniques are currently the most used for cesarean section. Spinal anesthesia is associated with higher incidence and more pronounced decreases in blood pressure compared with epidural anesthesia, and this is due to the earlier establishment of sympathetic blockade. Hypotension is the most frequent complication of spinal anesthesia in the pregnant woman and can be potentially dangerous for both the mother and the fetus, among these factors the most relevant are: Complete amniotic bag, which in term pregnancy can contain approximately more than 1,000 ml, which increases the compression exerted by the uterus on the vena cava and reduces in greater quantity the already deteriorated venous return, which favors arterial hypotension. The small stature in spite of the fact that the dose and the speed of administration of the local anesthetic in pregnant women is reduced with this characteristic, the length of the spine allows a high anesthetic level and therefore the appearance of arterial hypotension. The advanced age, as the age increases, the volume of the spinal and epidural space becomes smaller, reason why these patients develop greater cephalic propagation of the local anesthetic and greater tendency to hypotension17. Obesity increases the risk of arterial hypotension because this state develops greater supine hypotension and sympathetic activity, and further accentuates the aorto-cava compression, decreases the subarachnoid space and the pressure of cerebrospinal fluid, all due to the important deposit of fat in these regions, intra-abdominal pressure also increases with more cephalic displacement of the spinal block18